2015
DOI: 10.1111/febs.13176
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of yeast Crh1 and Crh2 transglycosylases

Abstract: Covalent cross-links between chitin and glucan at the yeast cell wall are created by the transglycosylase activity of redundant proteins Crh1 and Crh2, with cleavage of b-1,4 linkages of the chitin backbone and transfer of the generated molecule containing newly created reducing end onto the glucan acceptor. A three-dimensional structure of Crh1 was generated by homology modeling based on the crystal structure of bacterial 1,3-1,4-b-D-glucanase, followed by site-directed mutagenesis to obtain molecular insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 59 publications
1
29
0
Order By: Relevance
“…Double deletion of GAS1 and CHS1 or CHS3 (involved in chitin synthesis) resulted in a lysed-bud or a severely compromised phenotype (44), suggesting that both branched β-(1,3)-glucan and chitin are important in the cell wall. However, no such lethality has been described for the CRH1 CRH2 double deletion (45) [Crh1p and Crh2p are involved in linking chitin to β-(1,3)-glucan and β-(1,6)-glucan (46, 47), respectively], suggesting that glucan-chitin linkage may not be an essential part of the cell wall fibrillar core.…”
Section: Discussionmentioning
confidence: 99%
“…Double deletion of GAS1 and CHS1 or CHS3 (involved in chitin synthesis) resulted in a lysed-bud or a severely compromised phenotype (44), suggesting that both branched β-(1,3)-glucan and chitin are important in the cell wall. However, no such lethality has been described for the CRH1 CRH2 double deletion (45) [Crh1p and Crh2p are involved in linking chitin to β-(1,3)-glucan and β-(1,6)-glucan (46, 47), respectively], suggesting that glucan-chitin linkage may not be an essential part of the cell wall fibrillar core.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Crh1 and Crh2 would act as transglycosylases operating via a double displacement mechanism with retention of the anomericity of the formed glycosidic bond (Davies and Henrissat, ; Rye and Withers, ; Sinnott, ). The transglycosylase reaction catalyzed by these proteins involves the cleavage of the β‐1,4 linkages of the chitin and subsequent attachment of the fragment of the donor molecule through the newly formed reducing end onto the OH‐group of the acceptor molecule, presumably by a β‐1,4‐glycosidic bond (Blanco et al ., ) (Fig. B).…”
Section: Introductionmentioning
confidence: 86%
“…Site‐directed mutagenesis of amino acid residues at the catalytic domain of S. cerevisiae CRH1 and CRH2 genes and a respective functional analysis revealed that conserved residues within the catalytic domain acting as nucleophile and general acid/base residues (Fig. B) are essential for their transglycosylase activity (Blanco et al ., ; Blanco et al ., ). Therefore, Crh1 and Crh2 would act as transglycosylases operating via a double displacement mechanism with retention of the anomericity of the formed glycosidic bond (Davies and Henrissat, ; Rye and Withers, ; Sinnott, ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations